A Guerra que Portugal quis esquecer. Manuel Carvalho. Porto: Porto Editora, 2015, 270 pp., ISBN 978-972-0-06183-6 - Martins Pereira, Gaspar (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Recensão de A Guerra que Portugal quis esquecer. Manuel Carvalho. Porto: Porto Editora, 2015, 270 pp., ISBN 978-972-0-06183-6